2018
DOI: 10.3389/fmars.2018.00133
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA (eDNA) From the Wake of the Whales: Droplet Digital PCR for Detection and Species Identification

Abstract: Genetic sampling for identification of species, subspecies or stock of whales, dolphins and porpoises at sea remains challenging. Most samples have been collected with some form of a biopsy dart requiring a close approach of a vessel while the individual is at the surface. Here we have adopted droplet digital (dd)PCR technology for detection and species identification of cetaceans using environmental (e)DNA collected from seawater. We conducted a series of eDNA sampling experiments during 25 encounters with ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(185 citation statements)
references
References 42 publications
7
178
0
Order By: Relevance
“…In this study, the first of its kind, similar mitochondrial haplotype frequencies were recovered from seawater eDNA compared to tissue samples, expanding the applications of eDNA to encompass population genetics of aquatic organisms (Baker et al, 2018). A study by demonstrated the use of eDNA to provide estimates of genetic diversity in a whale shark (Rhincodon typus) aggregation off Qatar in the Arabian Gulf.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In this study, the first of its kind, similar mitochondrial haplotype frequencies were recovered from seawater eDNA compared to tissue samples, expanding the applications of eDNA to encompass population genetics of aquatic organisms (Baker et al, 2018). A study by demonstrated the use of eDNA to provide estimates of genetic diversity in a whale shark (Rhincodon typus) aggregation off Qatar in the Arabian Gulf.…”
Section: Introductionmentioning
confidence: 83%
“…However, in Iceland, conditions were calm and seawater samples were collected from a RIB following long encounters (1-2 hr) with killer whales, but again Feces are considered one of the highest sources of eDNA in environments (Alberdi et al, 2018;Baker et al, 2018;Klymus, Richter, Chapman, & Paukert, 2015), particularly for marine mammals whose feces are known to float (Gillett, Frasier, Rolland, & White, 2010;Stewart, 2019). However, in Iceland, conditions were calm and seawater samples were collected from a RIB following long encounters (1-2 hr) with killer whales, but again Feces are considered one of the highest sources of eDNA in environments (Alberdi et al, 2018;Baker et al, 2018;Klymus, Richter, Chapman, & Paukert, 2015), particularly for marine mammals whose feces are known to float (Gillett, Frasier, Rolland, & White, 2010;Stewart, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations